Five new and Nationally Threatened taxa of Brachyscome, Cardamine, Convolvulus, Geranium and Ranunculus obligate to vulnerable limestone habitats, eastern South Island, New Zealand - Heenan, Peter Brian; Molloy, Brian P.j. (Phytotaxa, 2019)
Four new species and one new forma are described from vulnerable and highly threatened calcareous habitats in eastern South Island, New Zealand. Brachyscome lucens is known from a limestone outcrop near Ward Beach, Marlborough. Cardamine magnifica is from Castle Hill Basin/Kura Tâwhiti, Canterbury, where it occurs on limestone scree and stony sites. Ranunculus callianthus is restricted to a limestone scarp in South Canterbury, where it is known from three subpopulations. Geranium socolateum occurs from South Canterbury to North Otago, and although relatively widespread usually occurs in small-sized populations. Convolvulus verecundus forma glaberrimus is known from one site in North Otago (Awahokomo), and is a glabrous-leaved variant of C. verecundus with which it is sympatric. Conservation status assessments are presented for Brachyscome lucens, Cardamine magnifica, Convolvulus verecundus forma glaberrimus, Geranium socolateum and Ranunculus callianthus, with all being assessed as Threatened, Nationally Critical.